Analysis of The Digital Printing Business Network of Business Entities Own Cicangkang Hilir Village - Resya Dwi Marselina; Vierla Aulia; Febry Reyhan Frizi; Ai Annisa Januarista (Pusat Riset dan Inovasi Nasional, 2024)
BUMDes (Village-Owned Enterprises) is an economic institution that regulates rural resources. Each village has the potential for both natural resources and human resources that need to be developed by BUMDes. One of the village potentials that needs to be maximized is graphic design services. One form of graphic design service is the Digital Printing business. Maximizing village potential can be done by establishing an extensive business network, so that any work that comes from the village quickly spreads and looks attractive to the general public. Therefore, this research tries to explore the application of the Digital Printing business in Cicangkang Hilir Village, starting from the application of business networks, production processes, marketing strategies, to the influence on the income of BUMDes Cicangkang Hilir. This research uses several concepts such as business networks, production, marketing strategies, and distribution channels. This research uses a qualitative descriptive research approach. The BUMdes studied in this research is called SERUMPUN, which has several Digital Printing products. SERUMPUN Has a business network, namely the Cicangkang Hilir Village Government and raw material suppliers. The production flow carried out by SERUMPUN is design selection, print production and finishing. SERUMPUN divides marketing segmentation based on geographic, demographic and psychographic segmentation. The marketing targets of cognate are local businesses, creative businesses, creative individuals, community organizations, community-based entrepreneurs, individuals who care about the environment, event markets, and weddings. SERUMPUN positions itself as a printing service business that shows creativity, innovation and social responsibility. SERUMPUN uses distribution channels, namely physical locations/printing outlets, Whatsapp, and digital payments. The presence of an extensive business network in the local area means SERUMPUN is able to develop a distribution network efficiently to connect their work to various sales points or strategic locations that have many customers. The presence of SERUMPUN turned out to be quite influential in increasing the income of BUMDes Cicangkang Hilir. A solid partnership network allows SERUMPUN to receive business promotion support from the government, and the opportunity to implement joint projects that have a broad impact on society.